Factores que influyen en la percepción de la calidad de atención de los usuarios del Hospital Provincial Martín Icaza” - Sánchez, Elida (2015)
The main objective of this research is to determine the factors that influence the perception of the quality of care provided in health services from external users of the Provincial Hospital "Martin Icaza". To do an observational-descriptive, correlational, cross-sectional study was developed, using an exit poll external users of emergency services, outpatient and hospitalization. The instrument was developed by the author, based on the assessment scale SERVQUAL, which was modified. The information was processed in the same database that were analyzed according to descriptive statistics to express them in charts and graphs. The results determined that patients have the following characteristics: mostly female 63.8%, 21.20% belongs to the group of 18-27 years of secondary education, from the urban area. The 54.61% of patients come to the hospital because it is free and no money to private health care. The overall average of the three services is in the category 3 to 3.9 which corresponds to regulate or agreement. Outpatient area achieved the best assessment of quality of care by the users while the lowest hospitalization service, this mismatch between quantitative and qualitative evaluation made